Pengaruh Kepemimpinan dan Pola Komunikasi Serta Lingkungan Kerja Non Fisik Terhadap Disiplin Kerja Pada Pegawai Dinas Pendidikan Daerah Kota Samarinda - Surahman Padhadiyatul Jensyah; Tetra Hidayati; Siti Maria (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
Surahman P. Jensyah. 2016. The Effect of Leadership And Communication Pattern And Also Non Physical Work Environment on Discipline Work in Official of Education and Culture Service Office of Samarinda Regency. The purpose of this study was to determine the influence of leadership, communication pattern and non physical work environment on official’s discipline work. The research was conducted at the Education and Culture Service Office of Samarinda Regency. The sampling method using probability/random sampling. Sampling respondents in this study amounted to 144 people. The analysis technique used is Multiple Linear Regression, analysis processed using SPSS version 22. The results of this study show that: 1) Leadership has a positive and significant effect on discipline work, 2) Communication pattern has a positive and significant effect on discipline work, 3) Non physical work environment has a positive and significant effect on discipline work.Keywords: Leadership, Communication Pattern, Non Physical Work Environment and Discipline Work.